Inovasi Produk Bernyit: Mendorong Ekonomi Hijau dan Kemandirian Ekonomi Masyarakat Desa Jeruk Soksok Binakal Kabupaten Bondowoso Melalui Revitalisasi Kerajinan Bernyit - Hosaini Hosaini; Muharofah Nur Safitri; Dahani Kusumawati (Jurnal Medika: Medika, 2025)
Program "Bernyit Product Innovation: Encouraging a Green Economy and Economic Independence for the Community of Jeruk Sok-Sok Binakal Village, Bondowoso Regency through the Revitalization of Bernyit Crafts"aims to improve the welfare of rural communities by strengthening a green economy based on local potential. This activity was motivated by the conditions of the people of Jeruk Sok-Sok Village, who mostly depend on bamboo-based Bernyit crafts for their livelihoods, but still face limitations in production technology, business management, and marketing. The implementation method uses a community-based approach.community-based participatorywhich actively involved the community in the planning, training, technological innovation, and evaluation stages. The results of the activity showed a 35% increase in work skills, a 45% increase in production efficiency thanks to the implementation of semi-automatic tools, and a 33% increase in production capacity. In addition, three independent artisan groups were successfully formed with a simple business management system and social media-based digital marketing. The discussion showed that the revitalization of Bernyit crafts not only strengthened the community's economy but also raised awareness of environmental sustainability principles. In conclusion, Bernyit product innovation serves as a model for developing a sustainable and independent green economy at the village level. The implication is that this program can be replicated in other regions to strengthen the natural fiber-based creative economy and support the achievement ofSustainable Development Goals(SDGs) especially in the aspects of decent work and green economic growth.